Sialic Acid on Avian Erythrocytes - Jankowski, Mark D. (Comp Biochem Physiol B Biochem Mol Biol, 2019)
Understanding variation in physiological traits across taxa is a central question in evolutionary biology that has wide-ranging implications in biomedicine, disease ecology, and environmental protection. Sialic acid (Sia), and in particular, 5-N-acetylneuraminic acid (Neu5Ac), is chemically bound to galactose and the underlying glycan via α2–3 or α2–6 glycosidic linkage (i.e., Siaα2–3Galactose or Siaα2–6Galactose), conferring two different cell surface structures that affects cell to cell communication and interactions with foreign agents including microparasites and toxins. As an initial step towards understanding variation of Sia across the class Aves, we collected red blood cells (RBCs or erythrocytes) and measured Sia quantity in 76 species and 340 individuals using HPLC-MS/MS and glycosidic linkage type in 24 species and 105 individuals using hemagglutination assay. Although Sia quantity did not, α2–6 glycosidic linkage did exhibit a discernable phylogenetic pattern as evaluated by a phylogenetic signal (λ) value of 0.7. Sia quantity appeared to be higher in after hatch year birds than hatch year birds (P<0.05); moreover, ~80% of the measured Sia across all individuals or species was expressed by ~20% of the individuals or species. Lastly, as expected, we detected a minimal presence of 5-N-glycolylneuraminic acid in the avian RBCs tested. These data provide novel insights and a large baseline dataset for further study on the variability of Sia in the class Aves which might be useful for understanding Sia dependent processes in birds.